A Modified Patch Antenna with Square-Open Loop Resonator Slot for Improved Bandwidth Performance in WiFi Applications - Rida Gadhafi; Mihai Sanduleanu (Advances in Science, Technology and Engineering Systems Journal, 2017)
A novel, modified square patch antenna with square open loop resonator slot, operating at 5.5 GHz, for improved bandwidth performance is proposed in this article. A complementary square open loop resonator is introduced on the patch to enhance the bandwidth more than twice that of the conventional square patch antenna operating at the same frequency. A prototype of the antenna operating at 5.5 GHz is designed and fabricated. Results show that 2:1 VSWR bandwidth of the antenna is 7% whereas the conventional square patch antenna offers only 3% bandwidth. The proposed antenna has a compact size of 1.9 cm x 2 cm. It offers a uniform gain of 4.25 dB and a directivity of 6.1 dB at the frequency of operation.
Keywords: Square patch antenna; Open loop resonator slot; Bandwidth enhancement